Fake News and the Individual. Personal Characteristics Which Influence What We Choose to Believe - Ovidiu CRISTIAN; Sebastian VAIDA (Studia Universitatis Babes-Bolyai, 2024)
As the phenomenon of fake news continues to increase and spread throughout the world, there is a need to understand how individual characteristics influence the propensity to believe in fake news. In this systematic review, we performed a search of relevant databases for scientific studies published starting with 2016, the year this term became mainstream, 2024. After applying inclusion and exclusion criteria, we selected ten studies, which showed that higher extraversion is related with an increased belief in fake news, while agreeableness, conscientiousness, and open-mindedness tend to protect against believing in fake news. A heightened state of emotionality (either negative or positive) is another individual characteristic which predisposes people to believe fake news. High intelligence individuals, but especially individuals with high analytical skills, who often use deep reflection (instead of their intuition/gut feeling) when processing information and making decisions, are the most protected when it comes to believing news that is not true.